ANALISIS PEMASARAN KARET POLA SWADAYA DI KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN - Nooky Anggita Sari; Evy Maharani; Eliza ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Agriculture Marketing is all commerce agent activities who connective the movement of agriculture food materials processed and raw material and also supply and demand, strarting from agriculture conducting until to final consumer, where this activities have an effect on to farmer, comission agent and factory. The purposes of this research are to analyse: rubber marketing channel, margin, and efficiency at self-supporting farmers in Pangkalan Kuras District Pelalawan Regency. This research started from February 2015 till July 2015. The research method who used in this research is survey method. The samples in this research used purposive sampling method with criteria of  rubber crop age ranging from 17-19 years old. Intake of sample to compiler and rubber factory used snowball sampling method by following it marketing channel. The result showed that only there were one marketing channel at self-supporting pattern that was from farmer - small compiler/agent - big compiler - factory. Ojol price buy which have been accepted by self-supporting rubber farmers equal toRp.6.172,32/Kg. Total value of margin marketing equal to Rp.1.527,68/Kg with total cost of marketing equal to Rp.1.538,83/Kg and marketing efficiency equal to 19,98 percent.   Keywords:Self-supporting pattern, marketing channel, margin, efficiency.